2014
DOI: 10.1002/cm.21202
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin isoforms support actomyosin biogenesis to generate contractile tension at the epithelial zonula adherens

Abstract: Epithelial cells generate contractile forces at their cell-cell contacts. These are concentrated at the specialized apical junction of the zonula adherens (ZA), where a ring of stabilized E-cadherin lies adjacent to prominent actomyosin bundles. Coupling of adhesion and actomyosin contractility yields tension in the junction. The biogenesis of junctional contractility requires actin assembly at the ZA as well as the recruitment of nonmuscle myosin II, but the molecular regulators of these processes are not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 55 publications
3
20
0
Order By: Relevance
“…Tropomyosin Co-localizes with Most Actin Structures Tropomyosins have been implicated in a variety of different actin structures, including stress fibers [6], lamellipodia [7], granules [11], endosomes [12], cortical actin [13], the epithelial zonula adherens [14], podosomes [15], the cleavage furrow of dividing cells [16,17], mitotic spindles [16], actin ruffles [18], short microfilaments associated with the Golgi [16,19], filopodia [8], and the endoplasmic reticulum [20]. Mammalian cells can produce over 40 different splice variants using four different tropomyosin genes, TPM1-4, and the resulting gene products can be divided into low-molecular-weight (LMW) isoforms that span six actin monomers and high-molecular-weight (HMW) isoforms that span seven actin monomers.…”
Section: Resultsmentioning
confidence: 99%
“…Tropomyosin Co-localizes with Most Actin Structures Tropomyosins have been implicated in a variety of different actin structures, including stress fibers [6], lamellipodia [7], granules [11], endosomes [12], cortical actin [13], the epithelial zonula adherens [14], podosomes [15], the cleavage furrow of dividing cells [16,17], mitotic spindles [16], actin ruffles [18], short microfilaments associated with the Golgi [16,19], filopodia [8], and the endoplasmic reticulum [20]. Mammalian cells can produce over 40 different splice variants using four different tropomyosin genes, TPM1-4, and the resulting gene products can be divided into low-molecular-weight (LMW) isoforms that span six actin monomers and high-molecular-weight (HMW) isoforms that span seven actin monomers.…”
Section: Resultsmentioning
confidence: 99%
“…Tpm1.7 promotes the formation of filopodia in B35 cells (Creed et al, 2011), which is dependent on the availability of active cofilin. In epithelial cells, Tpm3.1 is necessary for the stability of cell-cell junctions, and its deletion in mice greatly reduces the levels of junctional E-cadherin in the kidney (Caldwell et al, 2014). In addition to neurons, Tpm1.9 (also known as Tm5b) was shown to be essential for morphogenesis in a cell model of mammary gland differentiation (Zucchi et al, 2001), and Tpm1.1 (also known as alpha-Tm) is essential for development of the heart (Rethinasamy et al, 1998) Cell trafficking and cytokinesis…”
Section: Morphogenesismentioning
confidence: 99%
“…Tropomyosin (Tpm) was identified as a major component in integrin contractile units, and cells were incapable of forming contractions or sensing rigidity when Tpm2.1 protein levels were downregulated 14 . Recent discoveries have indicated that several types of tropomyosin, notably Tpm2.1 and Tpm3, were involved in E-cadherin adhesion integrity 41,42 . We found that Tpm2.1 accumulated in between E-cadherin-coated pillars in newly spread areas where CCs formed in the periphery of Cos-7 cells, which resembled its localization in integrin contractile units 14 .…”
Section: Myosin Iib and Tpm21 Mediate Cadherin Contractionmentioning
confidence: 99%